Problemi di geometria differenziale in grande Lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Sestriere (Torino), Italy, July 31-August 8, 1958 - Bompiani, E. (C.I.M.E. Summer Schools, 2011)
Lectures: C.B. Allendörfer: Global differential geometry of imbedded manifolds.- Seminars: P. Libermann: Pseudo-groupes infitésimaux.